Identification of 16S rRNA Gene and Detection of Some Virulence Factors in Multi-Antibiotic Resistant E. coli Isolated from Clinical and Water Samples - Zahraa Deyaa Sagban; Saba Jassim Jawad Al-Zubaidi (Tikrit Journal of Pure Science)
The study included collecting 140 clinical samples (urine, urine of patients with renal failure, burn swabs, wound swabs) from Baquba Teaching Hospital and Baladrooz General Hospital. 71 water samples were also collected from the Public Health Laboratory in Diyala Governorate to investigate the presence of E. coli bacteria. The bacteria were diagnosed morphologically, microscopically, by biochemical tests, and by Vitek device. 44 isolates of E. coli bacteria were obtained and their sensitivity to antibiotics was examined. The highest resistance was recorded to vancomycin (100 %), ampicillin and amoxicillin (86.4 %), and cefotaxime (84.2 %). The highest sensitivity was to ambienem and meropenem (100 %). The virulence factors were examined and the ability of bacteria to produce strong biofilms (16 %) from water samples, metallo-beta-lactamase (4 %), clinical (8 %) water, broad-spectrum beta-lactamase (20 %), clinical (4 %) water, and for the purpose of accurate diagnosis by molecular methods, bacteria were diagnosed using the 16S ribosomal RNA (16S rRNA) gene, as the isolates appeared at a rate of (100 %).